Construcción del discurso como base para generación de nuevo conocimiento en la educación superior (2019)
The experience of research involves the requirement of training and knowledge, mediated at the same time under a series of characteristics of who performs the generation of knowledge exercise. The present reflection develops three topics that go from the empirical dispositions of the researcher to the demand of the elaborated and structured discourse. For this purpose, initially, some antecedents that shape the daily life of the investigation are addressed. Next, the construction and legitimacy of the discourses that shape an institutionality of knowledge. Finally, it is interesting to gather the experience of the researcher in the elaboration of the research work in the processes of advanced education.